Appalachian Affects: Fieldwork as Material Ecology. (October 2020) - Gleason, Sean
This essay—based on fieldwork with off-grid homebuilders in the Mid-Ohio River Valley—recognizes ethnography as a more-than-human ecology of habit, rhythm, and affect. I begin by describing some of the materials, species, and affects I encountered during this fieldwork to show how Appalachian history, geography, and habit influenced my performance of sensory ethnography. From these anecdotes, field notes, and vignettes, I theorize ethnographic fieldwork as, first and foremost, a rhythmic attunement to place and bodies, especially nonhuman ones. In turn, I argue for a practice of fieldwork that roots human experience within a vibrant material ecology of more-than-human forces.